Best Answer

Both of these are straight line equations. So just find two points on the line, and connect with a straight edge.

- The first one: y = -3x + 4. Let y=0, and solve for x = -4/3, so the point (-4/3,0) is on the line.
- Let x=0 and solve for y = 4, so (0,4) is on the line. Connect those two points.

Do the same for the second line. Connect points (2/3,0) & (0,-2).

It looks like these two lines intersect at the point (1,1) on the graph. Plug in x=1 and y=1 and check if it satisfies both equations, and yes it does.

Q: How do you graph y equals -3x plus 4 with y equals 3x-2?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

(3x-4)(x+5)

x3+3x2+3x+2 divided by x+2 equals x2+x+1

3x = x + 4 x = 2 3x2=6 2+4=6

It is: 3x2+6x-11 = 0

No. Y=3X2+1 is a Binomial Equation.

Related questions

(a) y = -3x + 1

x2-5-4x2+3x = 0 -3x2+3x-5 = 0 or as 3x2-3x+5 = 0

3x2 + 22x + 7 = 3x2 +21x + x + 7 = 3x(x + 7) + (x + 7) = (x + 7)(3x + 1)

(3x-4)(x+5)

x3+3x2+3x+2 divided by x+2 equals x2+x+1

3x = x + 4 x = 2 3x2=6 2+4=6

It is: 3x2+6x-11 = 0

No. Y=3X2+1 is a Binomial Equation.

(3x + 2)(x + 2) so x = -2/3 or -2

3x*x = 3x2

3x2 + 2x - 8 = 0 is a quadratic equation.

3x2 + 5x + 2 is a quadratic expression that can be factored as follows: 3x2 + 5x + 2 = 3x2 + 3x + 2x + 2 = 3x(x + 1) + 2(x + 1) = (3x + 2)(x + 1)